Mass Mimicking Autoimmune Pancreatitis—A Report of Two Cases and Review of Literature - Shah, Diva S.; Prajapati, Bharat; Sanghavi, Kintan; Kanhere, Shubhda; Kothari, Jagdish; Dubal, Jignesh (Journal of Gastrointestinal and Abdominal Radiology, 2021)
Autoimmune pancreatitis (AIP) consists of two clinically histologically distinct forms (type I and II) of chronic pancreatitis that are histologically different. These forms of AIP classically respond to oral steroids. The focal form of AIP resembles pancreatic carcinoma both clinically and radiologically and it is of utmost importance to make an early correct diagnosis between these two diseases in order to identify the optimal therapeutic strategy and to avoid unnecessary laparotomy or pancreatic resection in AIP patients. Here we report focal forms of type I and II AIP with clinical and imaging features closely mimicking pancreatic carcinoma.
Keywords: autoimmune pancreatitis; pancreatic cancer; pancreatic adenocarcinoma; mass mimicking autoimmune pancreatitis